Bus deregulation in Great Britain : a review of the first year - 270146 Balcombe, R. J.; Hopkin, Jean M.; Perrett, Ken E.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research laboratory, 1988)
08